2003
DOI: 10.1002/polb.10427
|View full text |Cite
|
Sign up to set email alerts
|

Domain size equilibration in sphere‐forming block copolymers

Abstract: The kinetics of domain size equilibration were studied for asymmetric poly(ethylene‐alt‐propylene)‐b‐poly(dimethyl siloxane) (EPDMS) and polyisoprene‐b‐poly(dimethyl siloxane) (IDMS) block copolymers in the body‐centered cubic ordered phase. Small‐angle X‐ray scattering measurements of the principal peak position (q*) were made as a function of time after temperature jumps within the ordered state. The equilibration times were remarkably long, especially on cooling and for temperatures below 100 °C. For exampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
59
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(64 citation statements)
references
References 51 publications
5
59
0
Order By: Relevance
“…Theory (32,33) and experiments (34,35) show that the number density of micelle-like point particles increases with decreasing temperature, reducing the free unimer concentration and sharpening the local composition profile at the core-corona interface. The particle aggregation number (i.e., the number of diblock chains per particle) and particle volume increase slightly with decreasing temperature, as also occurs in the ordered BCC phase (36). At a certain temperature, the number density must saturate as the particles become tightly packed and the unimer concentration approaches zero.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Theory (32,33) and experiments (34,35) show that the number density of micelle-like point particles increases with decreasing temperature, reducing the free unimer concentration and sharpening the local composition profile at the core-corona interface. The particle aggregation number (i.e., the number of diblock chains per particle) and particle volume increase slightly with decreasing temperature, as also occurs in the ordered BCC phase (36). At a certain temperature, the number density must saturate as the particles become tightly packed and the unimer concentration approaches zero.…”
Section: Discussionmentioning
confidence: 99%
“…At this point, further cooling actually drives a reduction in particle number density due to the increasing core-corona interfacial tension, which favors larger spherical micelles (i.e., greater aggregation number). However, due to a high (and steeply temperature-dependent) energy penalty associated with transporting a core block through the corona region (∼exp[αχN]), single-chain diffusion across domains drops precipitously at reduced temperatures (36)(37)(38). This freezes collective particle-level reorganization necessary to accommodate the thermodynamic drive toward fewer, larger particles or the redistribution of particle volumes necessary to form the σ phase.…”
Section: Discussionmentioning
confidence: 99%
“…65 Therefore, the kinetics of phase transitions in dense suspensions can be very slow even if the exchange rate is fast. For instance, Cavicchi et al 66 observed very slow kinetics after temperature jumps within the body centered cubic (bcc) phase of polymer micelles, but rapid changes after jumps within the lamellar phase. Self diffusion of polymers in the system was fast in both cases.…”
Section: Dense Suspensionsmentioning
confidence: 99%
“…1 There are multiple mechanisms by which particles can undergo phase transitions and growth with the problem of characterizing a given system often approached using powerful, routine, but indirect in situ scattering techniques. [2][3][4][5][6][7][8] These methods provide an adequate bulk-averaged overview of the sample size and morphology based on assumptions of the nature of the nanostructures and theoretical fitting of the raw data. For many systems, including amphiphilic block copolymer (BCP) micelles, a delicate interplay exists between the kinetic and thermodynamic parameters, [9][10][11][12][13][14][15][16][17][18] which govern their size, morphology and dynamic behavior.…”
Section: Introductionmentioning
confidence: 99%
“…[25][26][27] However, we lack techniques for directly observing nanoparticle-by-nanoparticle dynamics and transformations as they occur. 5,7,8,22,[28][29][30][31][32][33] Typically, amphiphilic BCP assembly is performed via direct dissolution into a selective solvent, 2,24 or via gradual solvent exchange methods from common solvents to a solvent selective for one blocks. 11 After solvent-switch, and dependent on the preparation conditions, the assemblies will either equilibrate over time, forming the lowest free energy structure, or be kinetically trapped, yielding metastable morphologies and often resulting in the "freezing" of complex, and functionally desirable morphologies.…”
Section: Introductionmentioning
confidence: 99%